Monodisperse In2O3 nanoparticles synthesized by a novel solvothermal method with In(OH)3 as precursors. (April 2015) - Lin, Li-Tian; Tang, Li; Zhang, Rui; Deng, Chao; Chen, Dong-Ju; Cao, Li-Wei; Meng, Jian-Xin
Graphical abstract: Highlights: Monodisperse In2 O3 nanoparticles were synthesized by a novel solvothermal method. The particle size of In2 O3 nanoparticles is ultrafine, ∼5 nm. The precursor is readily available. It is free of any surfactant and template. The possible growth mechanism, delayed burst nucleation, are elucidated. Abstract: A novel solvothermal method has been developed for monodisperse In2 O3 nanoparticles (NPs) with ∼5 nm particle size, In(OH)3 as precursors and free of any surfactant and template. The NPs were characterized by X-ray diffraction (XRD), transmission electron microscopy (TEM), high-resolution TEM (HRTEM), energy-dispersive X-ray spectrum (EDS) and Fourier transform infrared spectrum (FT-IR). The temperature, the concentration of precursors and washing conditions dramatically affected the structure, morphology and size of NPs. The possible growth mechanism was elucidated as well, which was delayed burst nucleation. A weak quantum confinement effect of In2 O3 NPs resulting from the small particle size was observed in UV spectrum and one photoluminescence emission peak occurring in the visible region was detected as well.